O regime pluviométrico, o ritmo e as excepcionalidades das precipitações em Jataí – GO - Vasques, Hérika Silva (2017)
Considering climate as the yearly sequence of weather patterns, it may be viewed as ultimate result of the interaction between geographic variables, these being responsible for the atmospheric dynamics. Such acknowledgment contributes significantly to urban and rural planning, as it indicates, among other elements, precipitation, temperature variation, wind speed and direction, solar radiation, and relative humidity, which when associated to the surface, respond for various climatic phenomena. In this research, rainfall is highlighted as the true indicator of weather patterns in tropical savanna climates, such the case of the Goiás state. In this sense, the research had as main objective to analyze the rainfall regime and comprehend the sucession rate of atmospheric states of exceptional nature in the Jataí region, thus contributing to the climatic profiling of the researched area. This work was undertaken by mold of the Geographic Climatology, from quantitative (quartile deviation, central tendency distributions, Schroeder's pluviograms) and qualitative (rhythmic analysis) techniques. The study presents as conclusion the region's climatic regime and the atmospheric systems' participation table. The rainfall in Jataí is related, mainly, to frontal passings and action of an unstable Tropical-atlantic and Equatorial-continental air mass.